Comorbid depression is differentially associated with longitudinal medication nonadherence by race/ethnicity in patients with type 2 diabetes. Issue 25 (June 2016) - Axon, Robert Neal; Gebregziabher, Mulugeta; Hunt, Kelly J.; Lynch, Cheryl P.; Payne, Elizabeth; Walker, Rebekah J.; Egede, Leonard E.
Abstract : Abstract: The aim of the study was to examine whether depression impacts medication nonadherence (MNA) over time and determine if race has a differential impact on MNA in patients with type 2 diabetes and comorbid depression. Generalized estimating equations were used with a longitudinal national cohort of 740, 197 veterans with type 2 diabetes. MNA was the main outcome defined by <80% medication possession ratio for diabetes medications. The primary independent variable was comorbid depression. Analyses were adjusted for the longitudinal nature of the data and covariates including age, sex, marital status, and rural/urban residence. In adjusted models, MNA was higher in non-Hispanic blacks (NHBs) (odds ratio [OR] 1.58 [95% confidence interval—CI: 1.57, 1.59]), Hispanics (OR 1.34 [95% CI: 1.32, 1.35]), and the other/missing racial/ethnic group (OR 1.37 [95% CI: 1.36, 1.38]) than in non-Hispanic whites (NHWs). In stratified analyses, the odds of MNA associated with depression were highest in NHWs (OR 1.14 [95% CI: 1.12, 1.15]) and were significantly associated in the other 3 minority racial/ethnic groups. MNA was lower in rural than urban NHWs (OR 0.91 [95% CI: 0.90, 0.92]), NHBs (OR 0.92 [95% CI: 0.91, 0.94]), and the other/unknown racial/ethnic group (OR 0.89 [95% CI: 0.88, 0.90]), but higher in rural Hispanic patients (OR 1.12 [95% CI: 1.09, 1.14]). Depression was associated with increased odds of MNA in NHWs, as well as in minority groups, although associations were weaker in minority groups, perhaps as a result of the high baseline levels of MNA in minority groups. There were also differences by race/ethnicity in MNA in rural versus urban subjects.